2022
DOI: 10.1002/pc.27047
|View full text |Cite
|
Sign up to set email alerts
|

Redeemable environmental damage by recycling of industrial discarded and virgin glass fiber mats in hybrid composites—An exploratory investigation

Abstract: The fiber industry develops materials with good physical and mechanical characteristics, but it also generates a lot of waste that is difficult to degrade. Glass fibers can be extracted from waste glass fiber reinforced polymers because of advancements in grinding and sorting technologies. The objective of the current paper is to use waste glass fiber along with new woven glass fiber mat in structural application. Composites were manufactured using the hand layup method using virgin and discorded woven glass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[118] The potential for thermoplastic composites using jute fiber as reinforcing material was studied and by incorporating a fiber fraction of 50% increases bending strength by 49.97 MPa and tensile strength by 59.13 MPa. [119,120] 2.3.5 | Seed and fruit fiber Cotton, kapok, and coconut husk are common seed fibers extracted from the seeds of the respective plants and are used as reinforcements in bio-and nanocomposites. The development of a blend of seed fibers and its application in thermoset composite manufacture has introduced a new class of cellulose-based reinforcement material.…”
Section: Stalk Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…[118] The potential for thermoplastic composites using jute fiber as reinforcing material was studied and by incorporating a fiber fraction of 50% increases bending strength by 49.97 MPa and tensile strength by 59.13 MPa. [119,120] 2.3.5 | Seed and fruit fiber Cotton, kapok, and coconut husk are common seed fibers extracted from the seeds of the respective plants and are used as reinforcements in bio-and nanocomposites. The development of a blend of seed fibers and its application in thermoset composite manufacture has introduced a new class of cellulose-based reinforcement material.…”
Section: Stalk Fibermentioning
confidence: 99%
“…[ 118 ] The potential for thermoplastic composites using jute fiber as reinforcing material was studied and by incorporating a fiber fraction of 50% increases bending strength by 49.97 MPa and tensile strength by 59.13 MPa. [ 119,120 ]…”
Section: Materials Selection Criteriamentioning
confidence: 99%
“…The advancement of identical dissimilar components to present conventional metals, artificial materials and their respective alloys have been interesting research in present industrial and academic research investigation throughout the world. [1][2][3][4][5][6][7][8][9][10] Many industries are remunerating more interest to gathering carbon acclaims by decreasing pollutants to the environment. Utilizing natural sources to produce partially or fully biodegradable laminate is one small step against conserving the environment near us.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The hybrid composites are formed by interspersing multiple reinforcements in a single matrix. 10 One of the key benefits of composites is that the notion of hybridization offers the design engineer the ability to customize the material's qualities to specific needs. [11][12][13] Hybridization of lignocellulose fiber with stronger man-made fiber, such as glass or carbon, can enrich the stiffness, strength, and moisture-resistant qualities, thereby achieving a balance between environmental impact and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated that designing composites with two types of reinforcements offers exceptional characteristics 8,9 . The hybrid composites are formed by interspersing multiple reinforcements in a single matrix 10 . One of the key benefits of composites is that the notion of hybridization offers the design engineer the ability to customize the material's qualities to specific needs 11–13 .…”
Section: Introductionmentioning
confidence: 99%